What do community pharmacists do?: results from a work sampling study in London. (14th January 2014) - Davies, James E.; Barber, Nicholas; Taylor, David
Abstract Objective Government and professional groups within the pharmacy have sought to extend the role of pharmacists from dispensing‐focused towards the provision of further pharmaceutical services. The aim of this research was to describe how pharmacists in current English community pharmacy practice spend their time using a work sampling method. Methods Ten community pharmacies across London were purposively selected. Trained observers visited one pharmacy each to record the activities of the responsible pharmacist, using a fixed‐interval work sampling technique. Activities were recorded every minute, into one of 18 predefined, piloted and tested activity codes. Data were recorded for 4 h each day for 1 week at each pharmacy during 2011. Key findings A total of 12 306 observations were recorded across the pharmacies. The pharmacists spent the majority of their time assembling and labelling products (median 25.2%; quartiles 19.0, 31.0) and monitoring prescriptions for clinical appropriateness (10.6%; 8.3, 13.0). The next most prevalent activity code was rest, waiting and breaks (8.6%; 6.9, 15.3). They spent more time offering non‐prescription medicines advice (6.6%; 3.5, 7.6) than prescription medicines counselling (3.8%; 2.8, 5.6). The provision of pharmaceutical services accounted for 3.2% (0.8, 7.5) of pharmacists' time. Overall, 46.2 % (35.2, 56.2) of their time was spent on activities deemed to be 'Professional'. Conclusions Despite repeated attempts during the last decade to shift pharmacists' roles towards patient‐care activities, on the basis of this research, community pharmacists continue to spend the majority of their time on technical dispensing (as opposed to cognitive patient‐centred) tasks.